Hey Jude! Asking for the Original Situation and Message of a Catholic Epistle - Thurén, Lauri (New Testament studies, 1997)
The Epistle of Jude has been one of the most neglected texts in the New Testament, despite its simple structure and its candour. This neglect is partly due to its obscure historical situation.1 In this article, I shall approach the Epistle in a literary perspective in order to lay bare its first setting so that its message and theology can be analyzed more reliably. I contend that when the techniques of communication in Jude are clearly perceived, many typical pitfalls of interpretation will be avoided.